STRATEGI PENGELOLAAN DAN PENGEMBANGAN OBJEK WISATA BERBASIS PROMOSI DIGITAL: STUDI IMPLEMENTASI DAN DAMPAK PADA DESTINASI TELUKWANG SAKTI, DESA BIUKU TANJUNG - Sarinah; Mardalena; Anggia Pratiwi; Susanti; Sri Astuti (Hira Institute, 2025)
This study aims to analyze the implementation of digital promotion strategies in the management and development of Telukwang Sakti Tourism Objects in Biuku Tanjung Village, Merangin Regency, Jambi. The method used is a participatory qualitative approach with three main stages: pre-intervention, intervention, and post-intervention. The results of the study show that before the intervention, this tourist attraction experienced significant limitations in terms of promotion, did not have official social media, and did not have a clear branding identity. Through capacity training programs, creation of social media accounts (@telukwangsakti), creative content production, and branding development, there has been a significant increase in digital visibility and tourist visits. Within 1–2 months of implementation, Instagram followers increased from 0 to 450, the number of weekend visits increased from 40–60 to 70–100 people, and searches on Google Maps reached ±250 searches per month. This program has also succeeded in empowering the community through increasing digital literacy and management capacity. The conclusion of the study indicates that a digital promotion strategy based on community empowerment is not only effective in increasing tourist attractions, but also supports the sustainability of destination management. Recommendations are submitted to managers, local governments, and educational institutions in order to ensure sustainability and further development.